Psychological Flexibility in Depression Relapse Prevention: Processes of Change and Positive Mental Health in Group-Based ACT for Residual Symptoms - Østergaard, Tom; Lundgren, Tobias; Zettle, Robert D.; Landrø, Nils Inge; Haaland, Vegard Øksendal (Frontiers in Psychology, 2020)
Relapse rates following a depressive episode are high, with limited treatments available aimed at reducing such risk. Acceptance and commitment therapy (ACT) is a cognitive-behavioral approach that has gained increased empirical support in treatment of depression, and thus represents an alternative in relapse prevention. Psychological flexibility (PF) plays an important role in mental health according to the model on which ACT is based. This study aimed to investigate the role of PF and its subprocesses in reducing residual symptoms of depression and in improving positive mental health following an 8-week group-based ACT treatment. Adult participants (75.7% female) with a history of depression, but currently exhibiting residual symptoms (N = 106) completed measures before and after intervention, and at 6 and 12-month follow-up. A growth curve model showed that positive mental health increased over 12-months. Multilevel mediation modeling revealed that PF significantly mediated these changes as well as the reduction of depressive symptoms, and that processes of acceptance, cognitive defusion, values and committed action, in turn, mediated increased PF.